Problem Solving Thinking Skills: Effectiveness of Problem-Solving Model in Teaching Chemistry College Students - Utiya Azizah; Harun Nasrudin (Jurnal Penelitian Pendidikan IPA, 2022)
Problem-solving is considered one of the thinking skills that must be possessed in 21st-century education because problem-solving skills are needed to solve all problems that arise. This study aims to describe problem-solving thinking skills as a manifestation of the effectiveness of problem-solving models in college student chemistry learning. The research method uses descriptive research with a quantitative approach. The design used is One Group Pretest-Posttest Design.Â  This research was conducted in the chemistry department Universitas Negeri Surabaya with the subjects of 31 college students who programmed basic chemistry courses on chemical thermodynamics. Measurement of problem-solving thinking skills using a paper-pen test (pretest and posttest) in the form of an essay. This research findings show that: (1) Each indicator of problem-solving thinking skills of trained college students gets percentage, namely understanding problems 76.08%, planning problem solving 80.65%, implementing problem-solving 85.49%, drawing conclusions 78.50%, and evaluating problem-solving results 68.22%; and (2) N-gain scores for each indicator of problem-solving thinking skills obtained have medium and high criteria. Based on the research results, the problem-solving model has been effective in improving college students' problem-solving thinking skills.